The Pulmonary Embolism Response Team: Rationale, Operation, and Outcomes - Glazier, James J.; Patiño-Velasquez, Skarlet; Oviedo, Carlos (International Journal of Angiology, 2022)
The pulmonary embolism response team (PERT) is an institutionally based multidisciplinary team that is able to rapidly assess and provide treatment for patients with acute pulmonary embolism (PE). Intrinsic to the team's structure is a formal mechanism to execute a full range of medical, endovascular, and surgical therapies. In addition, the PERT provides appropriate multidisciplinary follow-up of patients. In the 10 years since the PERT was first introduced, it has gained acceptance in many centers in the United States and around the world. These PERTs have joined together to form an international association, called the PERT Consortium. The mission of this consortium is to advance the diagnosis, treatment, and outcomes of patients with PE. There is considerable evidence that the PERT model improves delivery and standardization of care of PE patients, particularly those patients with massive and submassive PE. However, it is not yet clear whether PERTs improve clinical outcomes. A large prospective database is currently being compiled by the PERT Consortium. Analysis of this database will likely further delineate the role of PERTs in the management of intermediate-to-high risk PE patients and, importantly, help determine in which PE patients PERT may improve clinical outcomes.
Keywords: pulmonary embolus; pulmonary embolism response team; multidisciplinary approach; rapid response team; interventional radiology; interventional cardiology